Sistem Pengembangan dan Pemberdayaan Budaya Organisasi di MIS Al-Iqro’ - Makmur Syukri; Fachruddin Fachruddin; Isma Hayati Dalayisma; Sulasmi Sulasmi (Tarbiatuna: Journal of Islamic Education Studies, 2023)
This study discusses the organizational development and empowerment system at MIS Al-Iqro. The research focus of this research is the system of development and empowerment in the madrasah. This study used qualitative research which explained descriptively regarding the development and empowerment of organizational culture in the madrasah. The data obtained from this study came from the head of the madrasa as the leader of the madrasa as well as its stakeholders such as deputy principals and teachers involved in organizational culture at the madrasa. While the technique of collecting data from interviews, observation as well as documentation related to the organizational structure of the madrasah. Keywords: Development, Empowerment, Organizational Culture.